EFEKTIVITAS SUHU DAN WAKTU PENYIMPANAN AIR MINUM ISI ULANG TERHADAP HASIL MOST PROBABLE NUMBER (MPN) COLIFORM - Zahra Amalia, Farah (Politeknik Kesehatan Kemenkes Bandung, 2024)
Refillable drinking water depots have currently become the most widely chosen source of water by the community due to their relatively affordable prices and easy accessibility around residential areas. However, the selection of these refillable drinking water depots can pose risks that can endanger health. Although they have undergone strict processing and packaging, there is a possibility that refillable drinking water can be contaminated by Coliform. One of the factors that can affect the level of Coliform contamination in refillable drinking water is the storage temperature and time.This study aims to determine the effectiveness of storage temperature and time of refillable drinking water on the results of the Most Probable Number (MPN) Coliform test. The type of research used is Quasi-Experiment. Refillable drinking water samples were taken from 30 houses around SMAN 1 Kota Sukabumi. The samples were divided into 2 storage temperature treatments (25°-30°C and 70°-80°C) with storage times of 3 days. The results showed that there was a significant influence between temperature and storage time treatments on the MPN Coliform results of refillable drinking water. The 70°-80°C temperature treatment with 1, 2, and 3 days of storage time resulted in the lowest MPN Coliform, while the 25°-30°C treatment with an average of 27.10°C and 3 days of storage time resulted in the highest MPN Coliform. It can be concluded that the storage of refillable drinking water at a temperature of 27.10°C for 3 days is the most effective treatment in determining the MPN Coliform.